Analisis Pengaruh Konten Digital YouTube terhadap Gaya Bahasa Anak-anak Usia Dini: Studi Kasus pada Anak Usia 3 dan 7 Tahun - Eka Zahrani Syaripuddin; Virda Syahrani; Abdul Haliq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of digital YouTube content on the language style of early childhood, focusing specifically on children aged 3 and 7 years. In the digital era, YouTube has become a widely accessed platform among children, serving as both an entertainment source and a learning tool. However, unsupervised consumption of content may impact children's language development and behavior. This research employs a qualitative approach using a case study method. Data were collected through observation, direct interviews with parents, and literature review from various academic sources. The findings reveal that the children's language style is significantly influenced by the type of content they frequently watch. Threeyear-old children tend to exhibit imitative and expressive language styles closely linked to physical actions, often mimicking scenes and dialogues from videos such as